Big sprockets and small-pitch chains: Advancements in transmissions for Olympic track cycling - Wragge-Morley, R.; Barnaby, G.; Burgess, S.; Hicks, B. (Journal of Science and Cycling, 2024)
Introduction It is well known that cycling is a sport in which the performance of the equipment is critical to the outcome of competitions. At the elite level, winning margins are very small. For example, in the men`s team pursuit at the Tokyo 2020 Olympics, the winning margin was 0.166 seconds against a time of 3 minutes 42 secs; in sprint events, the margins can be even smaller, the women`s individual sprint at the Rio 2016 Olympics was won by 0.016s and 0.004s in the two races of the final. Considerable effort is made by internationally competitive teams to ensure the best performance from athletes and equipment. The work described herein highlights some recent developments in the field of track bicycle transmissions, specifically related to the sizing and geometry of the chains and sprockets. The impact of these studies was quantified using a very accurate dynamometer and subsequently demonstrated in international competitions.